The photographs of Mário de Andrade with the robe - Casarin, Carolina (Revista do Instituto de Estudos Brasileiros, 2022)
The article presents an analysis of photographs of Mário de Andrade dressed in a robe at home. Stored in the IEB Archive, the “Lot Mário de Andrade at home” has nine photographic documents that portray the author of “Pauliceia desvairada” in his dressing gown at home, always in action. In the photographed scenes, the intellectual is surrounded by works of art, books, objects of study and work. By reviewing the publications through which these photos circulated, I intended to analyze the regimes of visibility of the writer's image projected by Mário de Andrade in these photographs, and the policy of the pose in the sense of affirming the place of the intellectual. This is an incipient research, to be developed within the scope of the postdoctoral program at the Instituto de Estudos Brasileiros USP.